"Pen and tongue" untied: Lillias Hamilton's uncensored view of ʿAbd al-Rahman Khan. Issue 1 (April 2020) - Kadrie, Namatullah
Abstract : Many Europeans went to Afghanistan in the 19th-century and entered the service of ʿAbd al-Rahman Khan, the Amir of Afghanistan (r. 1880–1901). Almost all of the Amir's employees abstained from publishing anything while inside the country; but upon leaving or escaping Afghanistan wrote voluminously about their experiences, which were critical of the Amir. Taking Lillias Hamilton, who served as court physician to ʿAbd al-Rahman from 1894 to 1897 as a case study, this paper argues that Hamilton practiced self-censorship, not only in Afghanistan, but after fleeing the country. Although Hamilton published a book and a large number of articles, and presented numerous talks after leaving Afghanistan, her publications and lectures intentionally eschewed any analyses of the Amir and focused instead on trivial matters. Only after the Amir's death in October 1901 did Hamilton do away with the mantle of self-censorship, and begin to express her polemical views of the Amir. These revelations, which include the Amir's despotic rule and unorthodox religious beliefs and practices, were not divulged while the potentate was alive lest it might bring about harm to her European counterparts who were still living in Kabul.